Textbook of international health: global health in a dynamic world. 3rd ed. - Birn, Anne-Emanuelle; Pillay, Yogan; Holtz, Timothy H. (New York, 2009)
"This classic text, formerly known as the "Basch" textbook, now completely revised in an updated new edition, brings together information that students and professionals working in the wide variety of disciplines concerned with international health will find in no other single source. It synthesizes historical, cultural, environmental, economic and political considerations to provide a comprehensive global overview of the many factors that determine the health of individuals and populations. The major determinants of health status in all regions of the world are discussed, and interventions undertaken at community, national, and international levels are described. The new edition features a renowned new authorship committed to updating and expanding the entire content while retaining the core elements of Basch's excellent text. "